원자층 증착법에 의한 TiO₂, Al₂O₃, 및 TiO₂-Al₂O₃ 나노라미네이트 박막이 316L Stainless Steel의 부식특성에 미치는 영향 - 이우재(Woo-Jae Lee); 만지흠(Zhixin Wan); 김다영(Da Young Kim); 장경수(Kyung Su Jang); 최현진(Hyun-Jin Choi); 최우창(Woo-Chang-Choi); 권세훈(Se Hun Kwon) (Biuletyn Uniejowski, 2017)
TiO2, Al2O3, and TiO2-Al2O3 nanolaminated films were grown by atomic layer deposition (ALD) on the 316L stainless steel (SS316L) substrates at a temperature of 150 ºC. The growth kinetics of ALD-TiO2 and Al2O3 thin films were systematically investigated in order to precisely control the thickness of each layers in the TiO2-Al2O3 nanolaminated films using a high-resolution transmission electron microscopy. And, the exact deposition rates of ALD-TiO2 on Al2O3 surface and ALD-Al2O3 on TiO2 surface were revealed to be 0.0284 nm/cycle and 0.11 nm/cycle, respectively. At given growth conditions, the microstructures of TiO2, Al2O3 and TiO2-Al2O3 nanolaminated films were amorphous. The potentiodynamic polarization test revealed that the TiO2-Al2O3 nanolaminated film coated SS316L had a best corrosion resistance, although all ALDcoated SS316L exhibited a clear improvement of the corrosion resistance compared with a bare SS316L. KCI Citation Count: 0